A utilização de jogos matemáticos no ensino de operações com frações no 6º ano do ensino fundamental em uma escola de Capanema/PA - OLIVEIRA, Gildson Gomes de (2022)
Studies and research prove the harsh reality of many children in Brazil and in several other countries in the world, when talking about difficulties in teaching and learning. Several reasons contribute to the student having learning difficulties, many are unable to learn to read, write, count and when these children enter school and this situation becomes a reality among teachers, these students are considered as backward and little intellectual development. When this lack of learning is related to the discipline of mathematics, then the problem becomes much more complex, since mathematics is considered to have knowledge and that most of the time the student is not prepared for his teaching. Thinking about a teaching proposal that can change, or create possibilities for changes to this situation, this work presents a methodological proposal that shows, in what concrete ways games provide understanding of mathematical concepts. The use of games in the classroom, besides being a playful and pleasant activity for the student, helps in the learning of mathematical concepts involved in situations generated through games, in which the student is instigated to make decisions and control the responses of his colleagues. Allowing the teacher to act as an advisor between their different actions. We tried to search for the origins of games in the learning of mathematics, making mathematics classes less methodical, helping the student to build his knowledge through concrete material, seeking playful methodologies that contribute to an effective learning on the part of students in mathematics.